Production of disperse particles of CdS from thiourea solutions in the presence of amino acids - Belikov, K.N.; Sofronova, E.M.; Matejchenko, P.V.; Babayevskaya, N.V.; Sofronov, D.S. (Functional Materials, 2013)
Synthesis of fine-dispersed particles of CdS by precipitation from thiourea solutions in the presence of different amino acids is carried out. It is found that the presence of ε aminocapronic, glutamic and n-aminobenzoic acids leads to the formation of small lamellar particles. Introduction of n-aminobenzoic acid in reaction mixture allows to increase a specific surface by 30 times.